Penjualan Peralatan Elektronik (Gadget) Menggunakan Aplikasi E-Dagang Atas Talian - Zulkarnain, Hassim (2008)
lnternet technology is a services provided by lnternet Services Provide (ISP) which allows every user to access the e-commerce and e-gadget application through web browser.The proposed application to develop is a new change in a process of selling product through internet if compare with conventional process. It only involved on verity of product display where there will be transaction process taken in place.Related to the product selection process until to product buying process, normally consumer will receive the product information through various advertising medium. With this e-commerce application, all product information would be given by the application owner which sell their product. Consumer can make an application for a selected product through on line. Other than that, it's also providing the calculation for cost of delivery, tax and other related expenses. The internet based business can improve the limitation of conventional business such as limited coverage, high risk and so on. E-commerce or internet based business are helping an individual who doesn't have enough time for shopping and it also will increase sales and marketing of the product. By having this system, it will give benefit to the customer and seller in a trusted value of business process.